Stable isotope analysis of the common periwinkle Littorina littorea depending on infection status and seasonality - Gronwald, Friederike; Bommarito, Claudia; Díaz-Morales, Dakeishla M; Manfrin, Alessandro; Martinez Reyes, Cindy; Nachev, Milen; Sures, Bernd; Weinberger, Florian (In: Gronwald, F et al. (2025): The diet contribution and habitat selection of the common periwinkle Littorina littorea depending on infection with parasites and seasonality [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974526, 2025)
Littorina littorea was collected at the study site. The foot of Littorina littorea was used for stable isotope analysis (δ15N and δ13C). The stable isotope composition of possible food sources was also determined. Samples were taken in spring, summer and autumn. For the analysis a diet tissue discrimination factor (DTDF) of 2.4 for δ15N and 1.0 for δ13C was subtracted, respectively. The data in the sheet are the raw data without the DTDF.
Keywords: Baltic Sea; Littorina littorea; parasite-host-system; Seasonality; stabe isotopes